BAG3-dependent noncanonical autophagy induced by proteasome inhibition in HepG2 cells - Liu, Bao-Qin (Landes Bioscience, 2013)
Emerging lines of evidence have shown that blockade of ubiquitin-proteasome system (UPS) activates autophagy. The molecular players that regulate the relationship between them remain to be elucidated. Bcl-2 associated athanogene 3 (BAG3) is a member of the BAG co-chaperone family that regulates the ATPase activity of heat shock protein 70 (HSP70) chaperone family. Studies on BAG3 have demonstrated that it plays multiple roles in physiological and pathological processes, including antiapoptotic activity, signal transduction, regulatory role in virus infection, cell adhesion and migration. Recent studies have attracted much attention on its role in initiation of autophagy. The current study, for the first time, demonstrates that proteasome inhibitors elicit noncanonical autophagy, which was not suppressed by inhibitors of class III phosphatidylinositol 3-kinase (PtdIns3K) or shRNA against Beclin 1 (BECN1). In addition, we demonstrate that BAG3 is ascribed to activation of autophagy elicited by proteasome inhibitors and MAPK8/9/10 (also known as JNK1/2/3 respectively) activation is also implicated via upregulation of BAG3. Moreover, we found that noncanonical autophagy mediated by BAG3 suppresses responsiveness of HepG2 cells to proteasome inhibitors.